Antibiofilm Ekstrak Etanol Biji Alpukat (Persea Americana) Terhadap Streptococcus Mutans (In Vitro) - Adzra Fadla; Selviana Wulansari (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: The most common oral disease in Indonesia is caries. Streptococcus mutans is the main cause of caries bacteria and has the ability to communicate with each other in biofilms. Avocado seeds (Persea Americana) contain flavonoids, saponins, alkanoids, terpenoids, steroids and tannins which have antibacterial activity. Objective: to determine the effect of ethanol extract of avocado seeds on S.mutans biofilm growth. Methods: the effect of ethanol extract of avocado seeds (P.americana) on the growth of S.mutans ATCC 25175 biofilm was evaluated by the crystal violet staining method carried out at the Micore Laboratory of Trisakti University. S.mutans bacteria were cultured using Brain Heart Infussion Broth (BHI-B) AT 37°C for 24 hours anaerobically. The ethanol extract of avocado seeds (P.americana) was diluted into 5 concentrations: 100%, 50%, 25%, 12.5%, and 6.25% with aquades. CHX (0.2%) became positive control and untreated biofilm became negative control. The extract was added to the well with a biofilm and incubated for 24 hours. The mass of the biofilm was measured by 0.5% crystal violet staining and the ethanol extract of avocado seeds (P.americana) from each concentration group and incubation period reduced the growth of S.mutans biofilm when compared with negative controls (p<0.05) . the best concentration to reduce biofilm adhesion was 12.5% with and incubation period of 24 hours. Conclusion: Avocado seeds (P.americana) ethanol ectract can inhibit the growth of S.mutans biofilm. More research is needed on other oral bacteria.